(untitled) (Teología, 2018)
In this Lectio Inauguralis the Dean propose to think of ways towards a more synodical faculty and a more prophetic theology. Synodality and prophecy are clues that include many institutional and theological questions. They reframe the historical figure of the institution and the balances in theological thinking. The “more” double (magis) points to the challenge of taking steps towards new goals, which means going from one less to another according to a metaphysics of participation, a theology of conversion, reformation or purification, and a path spirituality . The melius of a change aims to improve the good that exists. A positive change is a mutatio in melius. Saint Thomas teaches that reforms are oriented towards the best: in melius reformantur (ST I, 45, 1, ad 1um). He adds: “changes are specified and dignified not by their term a quo but by their term ad quem” (ad 2um). In each historical moment we must discern goals, projects, processes, reforms.